(untitled) (Research, Society and Development, 2025)
Introduction: The complete blood count (CBC) is one of the most frequently requested laboratory tests in clinical practice, and its reliability strongly depends on the pre-analytical phase, where errors related to patient preparation, blood collection, handling and transport of samples are most prevalent. Such errors may lead to misdiagnosis, delayed treatment and increased patient risk. Objective: To synthesize available evidence on the main pre-analytical errors related to CBC testing and to describe nursing care focused on patient preparation and prevention of these failures. Methodology: Integrative literature review conducted according to PRISMA recommendations, using national and international databases (MEDLINE, SciELO, LILACS and BDENF). Descriptors related to complete blood count, pre-analytical errors and nursing were used. Results and discussion: The studies showed that the most frequent pre-analytical errors involve inadequate patient preparation (fasting, medication use, positioning), prolonged tourniquet time, incorrect order of draw, inappropriate use of anticoagulants, hemolysis, insufficient sample volume, misidentification of patients and failures in recording essential information. Interventions such as standardized verbal instructions, illustrated educational materials, checklists, simulation-based training, digital forms and monitoring of quality indicators had a positive impact on reducing non-conformities. Final considerations: The pre-analytical phase of CBC testing is critical for patient safety and diagnostic accuracy. Qualified nursing practice, combined with the implementation of standardized protocols and ongoing education, is crucial to minimize errors and ensure reliable laboratory results.